1992
DOI: 10.1002/ijc.2910500606
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant interferon α‐2A combined with prednisone in metastatic renal‐cell carcinoma: Treatment results, serum interferon levels and the development of antibodies

Abstract: Five partial responses were seen in 23 patients with metastatic renal-cell carcinoma (MRCC) receiving interferon-alpha 2a (IFN)+prednisone (P). Four of 24 subsequent patients responded to IFN+P (combined response rate 19%). The median response duration was 8 months (3 to 30 months). The one-year survival for all eligible patients was 52%. Eight of 26 evaluable patients developed antibodies detected by an enzyme immunoassay. In 2 patients, high levels of neutralizing antibodies were also found, together with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Immune mechanisms are most often evoked as the mechanism of regression [2]. Interferon-a and Interleukin-2 have been shown to exert antitumour effects in a subset of patients with MRCC [2,8]. Interleukin-2 is presumed to activate T-lymphocytes, natural killer (NK) cells, lymphocyte-activated killer cells and tumour infiltrating lymphocyte cells as a mechanism of action.…”
Section: University Of Oslo Oslo Norwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Immune mechanisms are most often evoked as the mechanism of regression [2]. Interferon-a and Interleukin-2 have been shown to exert antitumour effects in a subset of patients with MRCC [2,8]. Interleukin-2 is presumed to activate T-lymphocytes, natural killer (NK) cells, lymphocyte-activated killer cells and tumour infiltrating lymphocyte cells as a mechanism of action.…”
Section: University Of Oslo Oslo Norwaymentioning
confidence: 99%
“…The necrotic areas in our patient's metastases before any therapy may indicate some degree of treatment-independent initiation of tumour regression. In this connection it is interesting that patients with MRCC respond to treatment with interferon-a even though the drug is combined with prednisone [8]. The role of glucocorticoids is therefore undefined in MRCC.…”
Section: University Of Oslo Oslo Norwaymentioning
confidence: 99%
“…reported that a combination treatment with interferon and prednisone for patients with metastatic renal cell carcinoma showed a similar response rate to interferon monotherapy, with significantly reduced subjective toxicity. 9 This is likely to apply to other immunotherapeutic agents, but it has not been demonstrated yet. Moreover, only very few cases have been reported in which steroids manifested antitumor effects against renal cancer in clinical settings.…”
Section: Discussionmentioning
confidence: 98%
“…Both are nonglycosylated recombinant proteins but differ in the amino acid at position 23: lysine in IFNα-2a and arginine in IFNα-2b. The incidence of antibody production has been reported to be higher in patients who receive IFNα-2a compared with patients who receive IFNα-2b [26].As shown in Table 1, studies have reported that from 19 % to 61 % of patients develop NAbs to IFNα-2a [4,11,13,14,26,30,33,37].…”
Section: Interferon α (Ifnα)mentioning
confidence: 94%